TINJAUAN ASPEK TEKNIK PEMBANGUNAN SUATU TERMINAL - Pingit Broro Atmadi (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2006)
Abstract Role Transportation of vital importance and strategic in development, hence planning and its development require to be compiled in unity of inwrought system. Terminal non a especial component in transportation system, but often represent medium costing money very big, and also represent node in road transportation network , as well as representing public service center, so that in its development need study technical, to be reached by a result of maximal and gratify as according to requirement. Terminal as place various facility utilize to support fluency a public transport transportation system, hence existence of terminal have to deflect be of benefit to society, governmental and also entrepreneur and operator Terminal development require to pay attention technique aspect, though aspect there still be other that is consideration from hokum aspect, economic and also politics and social. Technique aspect for example circulation movement traffic, facility, wide farm which available to various activity, and also parking system able to guarantee terminal operational fluency Key Words : Terminal, transportation system.